2021
DOI: 10.3390/ani11113085
|View full text |Cite
|
Sign up to set email alerts
|

Feather Pecking in Non-Beak-Trimmed and Beak-Trimmed Laying Hens on Commercial Farms with Aviaries

Abstract: Severe feather pecking (SFP) is a major animal welfare problem in layers. It results in pain and injuries in the affected animal. It was the aim of this study to gain insight into the actual pecking behavior of laying hens kept on commercial farms with flock sizes common in practice. We observed aggressive pecking and SFP in non-beak-trimmed and beak-trimmed flocks of laying hens and investigated possible influencing factors. The study took place on eight conventional farms in Germany with aviaries, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…During the laying period, the behavior of the animals was recorded in 3 observation periods ( OP ): OP 1 at the peak of the laying period between the 28th and 33rd wk of life, OP 2 in the middle of the laying period between the 42nd and 48th wk of life, and OP 3 at the end of the laying period between the 63rd and 68th wk of life ( Table 1 ). Additional information on the flocks is published in Schwarzer et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the laying period, the behavior of the animals was recorded in 3 observation periods ( OP ): OP 1 at the peak of the laying period between the 28th and 33rd wk of life, OP 2 in the middle of the laying period between the 42nd and 48th wk of life, and OP 3 at the end of the laying period between the 63rd and 68th wk of life ( Table 1 ). Additional information on the flocks is published in Schwarzer et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…As it was not possible to view all animals in the videos, we calculated the mean number of pecks per bird by dividing the total number of pecks observed in each observation period by the number of animals in the flock (severe feather pecking/bird, SFP/B ). The results of the pecking behavior are published in Schwarzer et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…This effect was significant for all EGs; however, it was most pronounced for NE. Other studies found the highest pecking rates in the litter area, as compared to perches and the nest box area in commercial laying hen flocks but did not observe aviary platforms [ 24 , 41 , 42 ]. The study of Elger, however, found a significant effect of the functional area “aviary platforms” on SFP in laying hens housed in commercial aviaries, compared to the functional areas “litter area” and “perches” [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the location of feather pecking in the housing system, the studies of Johnsen et al, and of Hansen, observed most feather pecking bouts on the perches, followed by the litter area and feeding platforms [ 22 , 31 ]. Other authors reported feather pecking predominantly in the litter area [ 24 , 41 , 42 ] or on the aviary platforms [ 43 ]. A layer of chick paper with food placed on top is usually put on the aviary slats before placing the pullets as part of the coccidiosis vaccination and feed-management strategy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The back, breast and neck regions are largely acknowledged in the literature as the areas in which feather pecking lesions are observed more frequently [ 31 , 32 , 34 , 35 , 36 ]. This increase in feather pecking behaviour in VM and reduction in FM compared to the control group, however, highlights an inconsistent effect of ramps on animal welfare, seeming to indicate that pecking is more present when vertical movement is allowed but lateral movement is limited (VM group), therefore in this group the (relatively) higher density and competition, although only in localized areas delimitated by partitions and likely at the higher end of the ramps, may have triggered feather pecking behaviour [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%